2016
DOI: 10.7754/clin.lab.2016.151201
|View full text |Cite
|
Sign up to set email alerts
|

Age and Gender Tailored Cutoff Value of hs-cTnT Contributes to Rapidly Diagnose Acute Myocardial Infarction in Chest Pain Patients

Abstract: Age and gender tailored cutoff value for hs-cTnT provides better diagnostic information, but yields no additional prognostic performance for risk prediction of death or major adverse cardiovascular events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 0 publications
0
3
0
3
Order By: Relevance
“…These findings were also consistent with a recent Chinese study in which sex-specific cut-offs were calculated in an original reference population and then further stratified according to age. This study reports an increased specificity for sex-related hs-cTnT thresholds in the diagnostics of AMI, as well as higher negative and positive predictive values [95]. However, the impact of age-stratification probably played a decisive role in this study, still highlighting a possible interplay between these two variables.…”
Section: Application Of Sex-specific Cut-offs In Clinical Practicementioning
confidence: 75%
“…These findings were also consistent with a recent Chinese study in which sex-specific cut-offs were calculated in an original reference population and then further stratified according to age. This study reports an increased specificity for sex-related hs-cTnT thresholds in the diagnostics of AMI, as well as higher negative and positive predictive values [95]. However, the impact of age-stratification probably played a decisive role in this study, still highlighting a possible interplay between these two variables.…”
Section: Application Of Sex-specific Cut-offs In Clinical Practicementioning
confidence: 75%
“…Another study showed that the downward adjustment of hs-cTn thresholds in women may be warranted to reduce the underdiagnosis of acute myocardial infarction in women [31]. It was also confirmed that revised cut-offs for hs-cTnT based on age and gender only improve the diagnostic performance rather than the prognostic risk prediction for death or other adverse events [32].…”
Section: Cardiac Troponinmentioning
confidence: 86%
“…However, the clinical benefit of sex-specific diagnostic thresholds remains unproven with recent reports finding no long-term survival benefit despite increased MI and injury diagnoses in women. 18,19,[21][22][23][24]…”
Section: Importancementioning
confidence: 99%